Against All Odds: Tentative Steps Toward Efficient Information Sharing in Groups - Darius Schlangenotto; Wendelin Schnedler; Radovan Vadovic (ZBW – Leibniz Information Centre for Economics, 2020)
When groups face difficult problems, the voice of experts may be lost in the noise of others' contributions. We present results from a "naturally noisy" setting, a large first-year undergraduate class, in which the expert's voice is "lost" to such a degree that it is in fact optimal for all non-experts to contribute their bits of information. A single individual has little chance to improve the outcome and coordinating with the whole group is impossible. In this setting, we examine the change in behavior before and after people can talk to their neighbors. We find that the number of people who reduce noise by holding back their information strongly and significantly increases.
Keywords: D71; D72; D81; D82; C99; 330; information aggregation; coordination; communication; swing voter's curse